Wakaf dalam Hukum Positif Indonesia: Analisis Yuridis-Normatif Terhadap Regulasi, Implementasi, dan Efektivitas Kesejahteraan - Nurhayati Masani; Roslan; Abubakar Mustafa; Basaria Nainggolan; Marwa (Al-Kindi, 2026)
Waqf has great potential to support social and economic welfare in Indonesia, but its implementation still faces various challenges. This article aims to analyze the regulation of waqf in Indonesian positive law, its implementation problems, and the effectiveness of regulations in improving public welfare. The research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that Law Number 41 of 2004 concerning Waqf has recognized cash waqf and productive waqf, but its implementation faces problems such as low certification of waqf lands, disputes with heirs, and regulatory limitations that restrict the space for the Indonesian Waqf Board (BWI). The effectiveness of waqf law is not yet optimal, as evidenced by the gap between waqf asset potential (IDR 3,500 trillion) and cash waqf realization (IDR 3.5 trillion). This research recommends revision of the Waqf Law, acceleration of waqf land certification, strengthening of public literacy, improvement of nazhir professionalism, and development of productive waqf models integrated with national development programs